Costs of seasonal influenza vaccination in South Africa. Issue 5 (30th March 2022) - Fraser, Heather; Tombe‐Mdewa, Winfrida; Kohli‐Lynch, Ciaran; Hofman, Karen; Tempia, Stefano; McMorrow, Meredith; Lambach, Philipp; Ramkrishna, Wayne; Cohen, Cheryl; Hutubessy, Raymond; Edoka, Ijeoma
Abstract: Background: Influenza accounts for a substantial number of deaths and hospitalisations annually in South Africa. To address this disease burden, the South African National Department of Health introduced a trivalent inactivated influenza vaccination programme in 2010. Methods: We adapted and populated the WHO Seasonal Influenza Immunization Costing Tool (WHO SIICT) with country‐specific data to estimate the cost of the influenza vaccination programme in South Africa. Data were obtained through key‐informant interviews at different levels of the health system and through a review of existing secondary data sources. Costs were estimated from a public provider perspective and expressed in 2018 prices. We conducted scenario analyses to assess the impact of different levels of programme expansion and the use of quadrivalent vaccines on total programme costs. Results: Total financial and economic costs were estimated at approximately USD 2.93 million and USD 7.91 million, respectively, while financial and economic cost per person immunised was estimated at USD 3.29 and USD 8.88, respectively. Expanding the programme by 5% and 10% increased economic cost per person immunised to USD 9.36 and USD 9.52 in the two scenarios, respectively. Finally, replacing trivalent inactivated influenza vaccine (TIV) with quadrivalent vaccine increased financial and economic costs to USD 4.89 and USD 10.48 per person immunised, respectively. Conclusion: We adapted the WHO SIICT and provide estimates of the total costs of the seasonal influenza vaccination programme in South Africa. These estimates provide a basis for planning future programme expansion and may serve as inputs for cost‐effectiveness analyses of seasonal influenza vaccination programmes.